A review on emerging negative capacitance field effect transistor for low power electronics. (October 2021) - Rahi, Shiromani Balmukund; Tayal, Shubham; Upadhyay, Abhishek Kumar
Abstract: Power consumption is the major concern for conventional CMOS based integrated circuit and systems. Since there is a scope of lowering supply voltage with steep-subthreshold swing field effect transistor (FET) devices, it has been advocated as a suitable candidate for future highly energy-efficient circuits and systems. Among all the developed and proposed low power FET devices, that possess subthreshold swing (SS) lesser than 60 mV/decade, the negative-capacitance FETs (NCFETs) have gained the major attention of scientific and academic communities. The concept of negative capacitance (NC) in FET is basically belongs to the amplify the internal potential without modification of transport phenomena. With this capability, the NCFET have achieved similar switching at lower supply voltage, V D D as compared to conventional MOSFETs. Property of achieving similar on-current ( I O N ) lower off-current ( I O F F ) at lower supply voltage indicates that NCFETs help to reduce the power consumption and switching voltage. This can be achieved by slight modification of conventional CMOS devices by adding thin layer of ferroelectric (FE) layer in gate stack. This slight modification in conventional MOSFET is for the NC, which is a special feature of FE materials. FE materials having nonlinear dielectric behavior. This material has preexisting, which is switched in reverse direction when an external electric field is applied. In this paper, a detailed review of NCFET device has discussed and also compared with the Tunnel FET (TFET) and conventional MOSFET.